Optimalisasi Infrastruktur Hijau sebagai Elemen Urban Ecological Network: Infrastruktur Hijau - By Nur Hidayah Rahmawati; Raksa Maulana Subki; Stephanie Arvina Yusuf; Rachmat Kurnia (Jurnal Syntax Fusion, 2026)
Rapid urbanization has resulted in landscape fragmentation, environmental degradation, and weakened ecological connectivity. The concept of the Urban Ecological Network (UEN) provides a systemic framework for integrating green spaces into a functional ecological system. Green infrastructure acts as the structural backbone of this network. This study aims to analyze the strategic role of green infrastructure in establishing UEN and to formulate optimization strategies for sustainable urban landscape planning. The research employs a qualitative-descriptive approach through a systematic literature review and conceptual analysis grounded in landscape ecology theory. The findings indicate that green infrastructure optimization requires spatial network planning, multi-scale integration, and regulatory alignment with ecological connectivity principles. Green infrastructure should be positioned as a core ecological structure rather than merely an aesthetic element in resilient urban systems.